A Mild and Eco-friendly, One-pot Synthesis of 2-hydroxy-Narylacetamides from 2-chloro-N-arylacetamides - Radhakrishna, Vamshikrishna Y.; Khatik, Gopal L.; Vijaya, Bhuvaneshwari S.; Nair, Vipin A. (Letters in Organic Chemistry, 2024)
A mild and eco-friendly one-pot, two-step procedure has been developed for the synthesis of 2-hydroxy-N-arylacetamides from 2-chloro-N-arylacetamides. The procedure overcomes the cleavage of the amide linkage in 2-chloroacetamides, which is usually observed under reflux conditions with the hydroxide when the nucleophilic substitution of the halide is attempted. The reactions were performed by refluxing 2-chloro-N-arylacetamides with Cu(OAc)2 and DIPEA in the ethanol medium to facilitate an acetate exchange with the halogen. Subsequently, by the addition of ethanolic KOH solution to the same reaction flask, the ester linkage was selectively cleaved in the presence of the amide, taking advantage of the difference in electrophilicity. The procedure afforded good yields of the desired products, which are valuable intermediates for several biologically active molecules, in a short reaction time with ease of isolation. The experimental conditions employed are simple and offer the possibility of scaling up to higher quantities.
Keywords: 2-chloro-narylacetamides